Plan de negocio para ATENEA accesorios - Velarde Marín, Alexandra Angélica (2021)
Recent events related to environmental pollution and struggles for equal opportunities have revolutionized the behavior of society. These events have driven consumer trends, as a result of which, the idea of this business plan was born, which seeks to generate profitability through the sale of innovative accessories for women, made with national raw materials and handmade by Peruvian artisans, but at the same time responsible with society and the planet. For the development of this study, surveys, two focus groups and personal interviews were carried out, which allowed to observe the main behaviors, preferences and motivations of consumers. Secondary databases were also used to study the behavior of the Peruvian market, the competition and the main stakeholders. Finally, marketing, sales, logistics and human resources strategies were stablished, wich allowed the financial analysis of the project.